Importance of the structural vulnerability of single-family housing in urban risk. Study model of Managua city, Nicaragua - Aguilar Arriola, Erasmo José (Revista de Urbanismo, 2016)
The detached house itself is the vital node of the city. In Managua, Nicaragua’s capital city, has many housing developments, especially popular housing or social housing which are offered in locations where the poorest classes are concentrated. Due to its characteristics, the exposure to natural hazards, and particularities of the most populated and busiest city in the country, the intensity of use creates a high level of urban risk. For this reason, it is essential to identify the contribution of the structural vulnerability of single-family homes to this urban risk. Generally, we did not notice the vulnerability of social interest housing, perhaps due to the lack of an appropriate methodology of study. However, if we use certain indicators to perform a health diagnosis of its structure, it becomes possible to make a contribution to the reduction of vulnerability in these Urbanization and urban risk.